EVALUASI KUALITAS PROSES REKAYASA KEBUTUHAN KNOWLEDGE ACQUISTION IN AUTOMATED SPECIFICATION MENGGUNAKAN MODEL âCONCERN OF REQUIREMENT ENGINEERINGâ - Adikara, Fransiskus (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
One of the most common methods used for goal-oriented requirements engineering is Knowledge Acquistion in Automated Specification (KAOS). In the previous research KAOS method has been used to develop a system. In this research, the Concern of Requirements Engineering (CORE) model is used to evaluate KAOS perspective and meet the criteria of research methods to improve the quality of the requirements engineering process. The objective of quality evaluation of KAOS process is to measure and assess the process quality of KAOS methods. The assessment result shows that KAOS method still need to complement its activities regarding to risk impact analysis, manage agreements for changing needs, and manage relationships between needs.